Epidemiological report on the treatment of patients with gestational trophoblastic disease in 10 Brazilian referral centers: Results after 12 years since international FIGO 2000 consensus - Braga, Antonio [UNESP]; Uberti, Elza Maria Hartmann [UNESP]; Fajardo, Maria do Carmo [UNESP]; Viggiano, Maurício [UNESP]; Sun, Sue Yazaki [UNESP]; Grillo, Bruno Maurizio [UNESP]; Padilha, Sérgio Lunardon [UNESP]; de Andrade, Jurandyr Moreira [UNESP]; de Souza, Christiani Bisinoto [UNESP]; Madi, José Mauro [UNESP]; Maestá, Izildinha [UNESP]; Silveira, Eduardo [UNESP] (My University, 2014)
OBJECTIVE: To evaluate treatment of Brazilian patients with gestational trophoblastic disease (GTD). STUDY DESIGN: A retrospective cohort study with analysis of medical reports performed in 10 Brazilian referral centers from January 2000 to December 2011. RESULTS: Of 5,250 patients 3 died (0.06%) at the time of uterine evacuation. Spontaneous remission of GTD (group G1) was observed in 4,103 cases, and 1,144 (21.8%) progressed to gestational trophoblastic neoplasia (GTN) (G2). In G1 2,716 (66.2%) had complete hydatidiform mole (HM) and 1,210, partial HM (29.5%); 3,772 patients (92.7%) recovered as noted in December 2012. In G2, of 1,118 patients treated, initial histopathological results of previous gestation were complete HM (77.5% [n=886]), partial HM (8.8% [n= 100]), and choriocarcinoma (8.0% [n=92]); 930 (81.3%) were low-risk, 200 (17.5%) were high-risk GTN, and 14 had placental site trophoblastic tumor (PSTT) (1.2%); cure was achieved in 1,078 cases (96.4%), but 26 patients (2.3%) died (4 lowrisk [0.4%], 19 high-risk [9.5%], and 3 PSTT [21.4%]). CONCLUSION: The highest death rates were due to high-risk GTN and PSTT. Patients with molar pregnancy should be referred to a referral center for an early diagnosis and prompt treatment of GTN in order to reduce the morbidity and mortality found in advanced stages.
Keywords: Epidemiology; Gestational trophoblastic disease; Gestational trophoblastic neoplasia; Hydatidiform mole; Placental site trophoblastic tumor